Global attractivity of the max-type difference equation xn = max{c, xn-1p/Σkj=2 xpjn-j} - Iričanin, Bratislav; Stević, Stevo (Utilitas Mathematica, 2013)
We show that positive solutions of the difference equation (Equation) with p, c ∈(0, 1), pj ≥ 0, j = 2, k, Σkj=2Pj = P, P2 ≤ P2, converge to one, improving and extending some results in the literature.